Participatory budgeting in the South African local government context : the case of the Mantsopa local municipality, Free State Province - Leduka, Moliehi (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.